2022
DOI: 10.1038/s41598-022-22282-1
|View full text |Cite
|
Sign up to set email alerts
|

Naïve pluripotent-like characteristics of non-tumorigenic Muse cells isolated from human amniotic membrane

Abstract: Multilineage-differentiating stress-enduring (Muse) cells are non-tumorigenic pluripotent-like stem cells that exhibit triploblastic differentiation and self-renewability at the single-cell level, and are collectable as pluripotent surface marker SSEA-3(+) from the bone marrow (BM), peripheral blood, and organ connective tissues. SSEA-3(+) cells from human amniotic membrane mesenchymal stem cells (hAMSCs) were compared with hBM-Muse cells. Similar to hBM-Muse cells, hAMSC-SSEA-3(+) cells expressed pluripotency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…Further studies are needed to elucidate the detailed mechanisms. The telomerase activity was reported to be lower in Muse cells than that in HeLa cells and iPSCs (27,29,65). Let-7a KD stimulated the proliferation but did not increase the telomerase activity, suggesting that let-7 is a key factor for controlling cell cycle but is not directly connected to tumorigenic proliferation in Muse cells.…”
Section: One Outstanding Difference Between Muse Cells and Escs Is Th...mentioning
confidence: 97%
“…Further studies are needed to elucidate the detailed mechanisms. The telomerase activity was reported to be lower in Muse cells than that in HeLa cells and iPSCs (27,29,65). Let-7a KD stimulated the proliferation but did not increase the telomerase activity, suggesting that let-7 is a key factor for controlling cell cycle but is not directly connected to tumorigenic proliferation in Muse cells.…”
Section: One Outstanding Difference Between Muse Cells and Escs Is Th...mentioning
confidence: 97%
“…Muse cells also exhibit reduced telomerase activity as well as increased capability for DNA repair [ 103 ]. Muse cells have been isolated from various locations, including the bone marrow (BM), connective tissues in various organs, as well as the amniotic membrane; these cells, like PSCs, are capable of differentiation into tissues from all three germ layers [ 104 ]. Use of Muse cells in animal models, including intravenous administration in a rabbit model of MI, revealed improvements in ejection fraction (EF), infarct scar size reduction and differentiation into relevant cell types [ 94 ].…”
Section: Stem and Progenitor Cell Therapies For Ischemic Heart Diseas...mentioning
confidence: 99%
“…Muse cells have also been utilized in human MI patients in a clinical study commenced in 2018; results showed improved ventricular function and reduced scar size, most likely due to direct cardiomyocyte differentiation as well as local paracrine effects. Nevertheless, only three patients were enrolled in this clinical study and were only followed for 12 weeks; thus, any possible tumorigenicity was not properly assessed [ 91 ], even though in general, Muse cells have been described as non-tumorigenic compared to other PSC types [ 104 , 106 ].…”
Section: Stem and Progenitor Cell Therapies For Ischemic Heart Diseas...mentioning
confidence: 99%
“…Muse cells derived from different sources such as BM, adipose tissue, dermis, and amnion consistently exhibit pluripotency gene expression, trilineage-differentiation ability, and self-renewal at a single-cell level [21,[35][36][37]. The differentiation tendencies differ among Muse cells [21,35]: Adipose tissue-Muse cells and dermis-Muse cells express higher levels of mesodermal-and ectodermal-lineage markers than BM-Muse cells, respectively, while amnion-Muse cells show higher potential to differentiate into germ-line and extraembryonic-lineage cells compared with BM-Muse cells [36].…”
Section: Introductionmentioning
confidence: 99%
“…Muse cells derived from different sources such as BM, adipose tissue, dermis, and amnion consistently exhibit pluripotency gene expression, trilineage-differentiation ability, and self-renewal at a single-cell level [21,[35][36][37]. The differentiation tendencies differ among Muse cells [21,35]: Adipose tissue-Muse cells and dermis-Muse cells express higher levels of mesodermal-and ectodermal-lineage markers than BM-Muse cells, respectively, while amnion-Muse cells show higher potential to differentiate into germ-line and extraembryonic-lineage cells compared with BM-Muse cells [36]. While Muse cells have also been harvested from UC [38] and preterm UC yields more vigorously proliferative Muse-cell source MSCs with a higher differentiation capacity than term UC [38][39][40], the basic characteristics and therapeutic effects of preterm-and term-UC-Muse cells have not been investigated.…”
Section: Introductionmentioning
confidence: 99%